Does perceived supervisor support reduce turnover intention? The mediating effects of work engagement among healthcare professionals. - Xiaolong, Tao; Gull, Nida; Asghar, Muhammad; Sarfraz, Muddassar; Jianmin, Zhang (Work, 2023)
BACKGROUND: The study's value is based on a complete understanding of the employee polychronicity–employee intention to leave the relationship in the health care sector. OBJECTIVE: This study examines (1) the role of job engagement in alleviating the relationship between employee polychronicity and intention to leave, and (2) the moderating impact of perceived supervisor support as a relationship. METHOD: This study employed a cross-cultural research design and collected data from nurses working in public sector hospitals. Through job engagement and perceived supervisor support (PSS), the effect of nurses' polychronicity on turnover intention was examined using the PLS-SEM approach. RESULTS: The findings of this study demonstrate that employee polychronicity has an impact on employee turnover. Employee engagement appears to operate as a mediator in the association between employee polychronicity and intention to leave and a moderating effect of PSS. CONCLUSION: By emphasizing employee engagement as a mediator and moderating role, the perceived supervisor supports the association between polychronicity and intention to leave of nurses. This study offered a crisp perspective on the complexities of the links between polychronicity, engagement, perceived organizational support, and employees' intention to leave.